Acinetobacter portensis sp. nov. and Acinetobacter guerrae sp. nov., isolated from raw meat. Issue 8 (3rd August 2020) - Carvalheira, Ana; Gonzales-Siles, Lucia; Salvà-Serra, Francisco; Lindgren, Åsa; Svensson-Stadler, Liselott; Thorell, Kaisa; Piñeiro-Iglesias, Beatriz; Karlsson, Roger; Silva, Joana; Teixeira, Paula; Moore, Edward R. B.
Abstract : The taxonomic status of six strains of Acinetobacter obtained from meat samples, collected from supermarkets in Porto, Portugal, was investigated using polyphasic analysis. Partial rpoB sequence similarities lower than 95 % to other Acinetobacter species with validly published names led to the hypothesis that these strains represented novel species. This was confirmed based on comparative multilocus sequence analysis, which included the gyrB, recA and 16S rRNA genes, revealing that these strains represented two coherent lineages that were distinct from each other and from all known species. The names Acinetobacter portensis sp. nov. (comprising four strains) and Acinetobacter guerrae sp. nov. (comprising two strains) are proposed for these novel species. The species status of these two groups was confirmed by low (below 95 %) whole-genome sequence average nucleotide identity values and low (below 70 %) digital DNA–DNA hybridization similarities between the whole-genome sequences of the proposed type strains of each novel species and the representatives of the known Acinetobacter species. Phylogenomic treeing from core genome analysis supported these results. The coherence of each new species lineage was supported by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry differentiation of the species at the protein level, by cellular fatty acid profiles, and by unique and differential combinations of metabolic and physiological properties shared by each novel species. The type strain of A. portensis sp. nov. is AC 877 T (=CCUG 68672 T =CCM 8789 T ) and the type strain of A. guerrae sp. nov. is AC 1271 T (=CCUG 68674 T =CCM 8791 T ).